Mapping Environmental Hidden Curriculum in Physics Learning - Yumelda Marzuki; Desnita Desnita (Postgraduate, University of Mataram, 2023)
Environmental problems that occur today have reached an alarming level. Global warming, flooding in the rainy season, and summer drought are environmental problems troubling people. These problems result from human behavior that is not wise in managing the environment. The trigger for this problem is human behavior, so the solution is to change behavior. Changes in human behavior toward the environment can be done by integrating various subjects, such as a